2001
DOI: 10.1175/1520-0450(2001)040<0005:copwoi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Precipitable Water Observations in the Near Tropics by GPS, Microwave Radiometer, and Radiosondes

Abstract: The sensing of precipitable water (PW) using the Global Positioning System (GPS) in the near Tropics is investigated. GPS data acquired from the Central Weather Bureau's Taipei weather station in Banchao (Taipei), Taiwan, and each of nine International GPS Service (IGS) stations were utilized to determine independently the PW at the Taipei site from 18 to 24 March 1998. Baselines between Taipei and the other nine stations range from 676 to 3009 km. The PW determined from GPS observations for the nine baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 20 publications
8
93
0
5
Order By: Relevance
“…대기 중에 존재하는 수증기의 양은 매우 적지만 복 사과정을 통한 대기의 에너지 전달 뿐만 아니라 구름 의 형성·소멸, 강수, 지표증발산 등 수문학적 순환 (hydrologic water cycle)을 통해 기후에도 큰 영향을 미친다 (Chahine, 1992) 라디오미터 관측 자료의 품질은 주로 라디오미터의 연직 가강수량값과 라디오존데에서 산출된 가강수량 값의 비교를 통해 판단되며 많은 연구를 통해 검증 이 이루어졌다 (Baelen et al, 2005;Hogg et al, 1983;Liou et al, 2001). 국내에서도 해남(Radiometrics, TP/WVP-3029A)과 대관령(Radiometrics, WVR-1100) 에 설치된 라디오미터 관측 자료의 검증연구가 수행 되었다 (전은희 외, 2008; 양하영 외, 2010 (Fig.…”
Section: 서 론unclassified
“…대기 중에 존재하는 수증기의 양은 매우 적지만 복 사과정을 통한 대기의 에너지 전달 뿐만 아니라 구름 의 형성·소멸, 강수, 지표증발산 등 수문학적 순환 (hydrologic water cycle)을 통해 기후에도 큰 영향을 미친다 (Chahine, 1992) 라디오미터 관측 자료의 품질은 주로 라디오미터의 연직 가강수량값과 라디오존데에서 산출된 가강수량 값의 비교를 통해 판단되며 많은 연구를 통해 검증 이 이루어졌다 (Baelen et al, 2005;Hogg et al, 1983;Liou et al, 2001). 국내에서도 해남(Radiometrics, TP/WVP-3029A)과 대관령(Radiometrics, WVR-1100) 에 설치된 라디오미터 관측 자료의 검증연구가 수행 되었다 (전은희 외, 2008; 양하영 외, 2010 (Fig.…”
Section: 서 론unclassified
“…The observation values of radiosonde which has been used for the longest period of time are used often for verification, calibration and analysis of characteristics for values measured by other systems. For example, in a relative comparison with values measured by MWR, average difference from radiosonde results was represented as 1-5 mm, and standard deviation was represented as 1-2 mm (Westwater et al 1989, Liou et al 2001, Basili et al 2002, Pacione et al 2002, and in a relative comparison with values measured by GPS, average difference from radiosonde results was represented as 1-4 mm, and standard deviation was represented as 1-5 mm (Moon et al 1999, Kwon et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies demonstrated that the site-specific T M model is greater than the regional T M model (Liou et al, 2001;Suresh Raju et al, 2007;Singh et al, 2014). The site-specific T M model is accurately tuned to site-specific weather condition at single GPS station only which is in contrast to regional T M model that take account of the variability of weather over a large coverage area.…”
Section: Case 2: Site-specific Versus Regional T M Modelsmentioning
confidence: 99%
“…A commonly used method to estimate the T M parameter; (1) to apply a regression function from the relationship of surface air temperature (TS) as described by Musa et al, (2011) and Liou et al, (2001), (2) reanalyses the output from numerical weather prediction model such as Jin et al, (2009) and Heise et al, (2009), (3) estimate by using the Global Pressure and Temperature (GPT) model developed by Boehm et al, (2007) (Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%